Hermansky–Pudlak Syndrome - De Jesus Rojas, Wilfredo; Young, Lisa R. (Seminars in Respiratory and Critical Care Medicine, 2020)
Hermansky–Pudlak syndrome (HPS) is a multisystemic autosomal recessive disorder characterized by oculocutaneous albinism, bleeding diathesis, and lethal pulmonary fibrosis (PF) in some HPS subtypes. During middle adulthood, ground-glass opacities, reticulation, and traction bronchiectasis develop with progression of PF. HPS is an orphan disease occurring in 1 in 500,000 to 1,000,000 individuals worldwide, though the prevalence is 1 in 1,800 in individuals with Puerto Rican heritage. Recessive mutations or disruptions in HPS genes alter the function of HPS proteins which are components of biogenesis of lysosome-related organelle complexes and are critical for intracellular protein trafficking. Diagnosis and management of HPS-related comorbidities represent a challenge to physicians, and a multidisciplinary clinical approach is necessary for early detection, health management, and surveillance of PF in patients with HPS types 1, 2, and 4. Treatment options for individuals with HPS-PF include pirfenidone and lung transplantation. In this article, we describe the epidemiology, genetics, clinical manifestations, and management of HPS.
Keywords: Hermansky–Pudlak syndrome; pulmonary fibrosis; oculocutaneous albinism; interstitial lung disease; bleeding diathesis; rare disease